Social support and general self-efficacy: Two predictors of quality of life at work in Ecuadorian teachers - Jaguaco, Diego; Turpo-Chaparro, Josué; Vásquez-Villanueva, Salomon; Apaza-Romero, Abel (Frontiers in Education, 2022)
The quality of life at work has been affected by the COVID-19 pandemic, generating labor overload, higher levels of stress and reduction in workers' productivity. In the education sector, thousands of teachers were affected by the change to a new online work modality and the acquisition of new work tools. The aim of this study was to determine whether social support and general self-efficacy significantly predict quality of life at work in a group of Ecuadorian teachers. 300 teachers of both sexes participated in the study, whose ages fluctuated between 21 and 64 years. For measurements, it was used: the Duke-UNK-11 General Sale Scale Scale and the Scale of Quality of Life in the CVT-Gohisalo Work. The predictive analysis was through linear regression. The results showThe results show a moderately significant relationship between social support, general self-efficacy, and quality of life at work. Likewise, the multiple regression analysis confirms that social support and self-efficacy are variables that significantly predict quality of life at work. The findings of this research also confirm that teachers with higher levels of general self-efficacy report higher levels of quality of work life. In conclusion, the prediction of the variables social support and general self-efficacy in the quality of life at work of Ecuadorian teachers is confirmed. The implications of the predictive model mediating quality of life at work are discussed.